The secret meal of Antarctic mesopelagic fish (Myctophidae: Electrona) revealed by multi-marker metabarcoding - Ruiz, Micaela Belen; Saunders, Ryan Alexander; Tarling, Geraint A.; Murray, Ayla; Leese, Florian; Havermans, Charlotte (Frontiers in Marine Science, 2024)
Introduction In the Southern Ocean, myctophids are the most successful pelagic fish group in terms of diversity, biomass, and abundance. They play a crucial role in linking primary consumers and coupling carbon flux between surface and mesopelagic depths. Understanding their trophodynamics is key to assessing pelagic ecosystem resilience under environmental change. Conventional stomach content analyses indicate that myctophids predominantly feed on crustaceans, such as copepods and euphausiids, but are less effective at detecting easily digestible, soft-bodied organisms like gelatinous zooplankton (GZP) and pteropods. Methods This study used multimarker (COI Leray-XT and 18S v1-v2) DNA metabarcoding to analyze the diets of two abundant myctophids in the Scotia Sea, Electrona antarctica and Electrona carlsbergi. Results and discussion We found a diverse diet dominated by copepods and euphausiids, followed by pteropods and GZP in terms of frequency of occurrence and relative read abundances. Within the GZP, salps and appendicularians were major components of the diet for E. carlsbergi, while hydrozoans were prominent in E. antarctica. With regards seasonal and spatial variability in the dietary contribution of GZP, E. carlsbergi consumed primarily appendicularians, chaetognaths, and hydrozoans during spring (2006) in the northern region, and more salps (predominantly Ilhea racovitzai) and other cnidarians in autumn (2009) in the southern region. Our study reveals the dietary diversity of myctophid fish as well as the importance GZP consumption as a key trophic pathway in the Southern Ocean.